1999
DOI: 10.1021/np990261q
|View full text |Cite
|
Sign up to set email alerts
|

O- and N-Methylation in the Biosynthesis of Staurosporine

Abstract: The feeding of (13)C- and (2)H-enriched methionine to Streptomyces staurosporeus established that the methyl carbon and proton source of both the 3'-O- and 4'-N-methyl groups of staurosporine (1) was methionine and that all three methyl protons from methionine were retained on 1. In the presence of the methyltransferase inhibitor, sinefungin, the biosynthesis of staurosporine was blocked at the last step, O-methylation. An intermediate, 3'-demethoxy-3'-hydroxystaurosporine (2), was efficiently accumulated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Streptomycetes produce a variety of bioactive polyketides, many of which contain methyl groups introduced via the action of N-and O-methyltransferases (16,66). PhzM most closely resembles O-methyltransferases from Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Streptomycetes produce a variety of bioactive polyketides, many of which contain methyl groups introduced via the action of N-and O-methyltransferases (16,66). PhzM most closely resembles O-methyltransferases from Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…7) Biosynthetic studies done with isotope-labeled precursors indicated that the indolocarbazole structure is derived from two molecules of tryptophan, probably via indolepyruvic acid as an intermediate. [8][9][10] Ohuchi et al reported cloning of the ngt gene encoding an Nglycosyltransferase from L. aerocolonigenes ATCC 39243. 5) The Ngt protein converted an indolocarbazole, J-104303, to its N-glucoside, indicating that ngt is responsible for N-glycosylation in rebeccamycin biosynthesis.…”
Section: Characterization Of the Biosynthetic Gene Cluster Ofmentioning
confidence: 99%
“…PhzM is a predicted 36-kDa protein similar to enzymes involved in the methylation of polyketide antibiotics by Streptomyces spp. (60). Though the 1.8-Å crystal structure of PhzM from P. aeruginosa was determined by single-wavelength anomalous dispersion (40), little is known about the features of phzM gene expression and regulation in pseudomonads.…”
mentioning
confidence: 99%